Analisis Waktu pada Pekerjaan Tambahan Proyek Pembangunan Gedung PT. Petrokimia Gresik - Nurafifah, Nabilah Mawadah; Dewita, Hikma; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The time analysis of the additional work of the PT. Petrokimia Gresik Building Construction project aims to determine the delay and acceleration during the implementation of additional work to meet the SLF (Certificate of Functioning) requirements on the work items of emergency stairs, fire extinguisher, GWT and electrical which have a contract value of Rp 3,556,641,848, - with a planned project completion time of 19 weeks located on Jl. Tanah Abang II no. 63, Central Jakarta, DKI Jakarta. In this study using the Earned Value Concept method, which is a method that can analyze time and provide an overview of conditions at the time of realization which includes indicators in the form of BCWS and BCWP. At the time of the implementation of the additional work, in fifth weeks to twelveth seen from the value of the schedule variant (SV) shows a positive number (+) which means the work is carried out faster than planned. However, the evaluation of week 15 to week 17 seen from the schedule variance value (SV) has a negative value (-) which means there is a delay from the plan schedule at the time of implementation. But the delay did not really affect the project completion time at the end because previously there was an acceleration of work. At the end of the SPI calculation, it has a value of 1 = 1, which means that the work implementation time is in accordance with the planned time of 19 weeks.